Secretions and Exudates in Biological Systems - Vivanco, Jorge M.; Vivanco, Jorge M.; Baluška, František.; Baluška, František. (Signaling and Communication in Plants,, 2012)
Secretions and emissions in biological systems play important signaling roles within the organism but also in its communications with the surrounding environment.  This volume brings together state-of-the-art information on the role of secretions and emissions in different organs and organisms ranging from flowers and roots of plants to nematodes and human organs. The plant chapters relate information regarding the biochemistry of flower volatiles and root exudates, and their role in attracting pollinators and soil microbial communities respectively. Microbial chapters explain the biochemistry and ecology of quorum sensing and how microbial communities highly co-adapted to plants can aid in bio-energy applications by degrading ligno-cellulosic materials. Other chapters explain the biology of secretions by nematodes, algae and humans, among other organisms. This volume will be a welcome addition to the literature, as no other book covers aspects related to biological secretion in such a holistic and integrative manner.